Choice of self employment intention among secondary school students - Lope Pihie, Zaidatol Akmaliah; Hassan, Hisyammudin (The Journal of International Social Research, 2009)
Entrepreneurial research among secondary school students has become more important for the past two decades. In line with the government emphasis on entrepreneurship as an important career option as a source of national prosperity in the future, this study is to investigate the status of secondary school students’ selfemployment intention based on the Theory of Planned Behavior. The study was tested on a sample of 1357 students in Klang Valley area which random sampling method was utilized. The instrument with 5 Likert Scales used has a reliability value with a Cronbach a range between .65 and .96. The results showed significant and positive correlations between attitudes towards self-employment, subjective norms, support, entrepreneurial selfefficacy and interest with self-employment intentions. In fact, subjective norm showed the strongest relationship with self-employment intentions (r=.68; p<.01) and attitude depicted the lowest (r=.40; p<.01). The finding also revealed that community support had a strong relationship with intention (r=64; p<.01). Based on the findings, even though all factors had a significant relationship with self-employment intentions, subjective norms showed the strongest relationship with entrepreneurship as a career for secondary school students.